InP and Sn:InP based quantum dot sensitized solar cells - Yang, Suolong; Zhao, Pengxiang; Zhao, Xiaochong; Qu, Liangti; Lai, Xinchun (Journal of materials chemistry. A, Materials for energy and sustainability, 2015)
Due to the ideal band gap and environmental friendliness, InP is a promising light-harvesting material in photovoltaic cells. However, “green” InP based quantum dot sensitized solar cells (QDSSCs) have been rarely reported. Herein, nearly monodispersed Sn doped InP (Sn:InP) quantum dots (QDs) were synthesized by the one-pot nucleation doping method, and used as the sensitizer in the construction of QDSSCs. High QD loadings on the TiO 2 film electrodes were achieved by using the capping ligand-induced self-assembly (CLIS) sensitization technique. The resulting champion Sn:InP cell shows a power conversion efficiency (PCE) of 3.54% under AM 1.5G (simulated 1 sun illumination), which is remarkably higher than that of un-doped InP QD based ones. This improvement is ascribed to the regulation role of the band gap by Sn dopant in the InP QDs. The Sn:InP QDSSCs exhibit moderate efficiency, good reproducibility and stability. These new findings may pave the way for the performance improvements of other QD photovoltaic devices.